Marriage and Family in stories about celebrities. Covers of ¡Hola! (2000-2004) - Mercado Sáez, María Teresa (2012)
Legal changes about family Law in Spain are important in recent past. One reason for this is the social change with a predicable storytelling in the Press. Relationships, engagements, marriages and families are an important content in gossip press, so this paper wants to measure their presence in this kind of press. That’s why this study analyzes the selection of news and their values in the covers of the most important Spanish gossip magazine, ¡Hola! from 2000 to 2004, the period of legal changes.